Successful Implementation of Breastfeeding at Workplace: Review of Practical Knowledge and Skill for Female Workers - Ray Wagiu Basrowi; Tonny Sundjaya; Erika Wasito (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Introduction: Working mother has less time to breastfeed, increasing the risk of breastfeeding discontinuation and exclusive breastfeeding. This can impact the health of both mother and child.Objective: This review aims to discuss the factors for successful breastfeeding in working motherDiscussion: The factors influencing breastfeeding practices among working mothers are exclusive breastfeeding practice and workplace factors. The mother’s intention to breastfed is the most critical factor in ensuring successful breastfeeding for working mothers. Preparation required when breastfeeding mothers return to work are breastfeeding strategic plan, stress management, attitude towards breastfeeding, family support, support from the work environment, and expressing breastmilk. Meanwhile, the things that need to be prepared when mothers breastfeed at work are pumping and storing equipment, supporting work environment and facilities, hygiene practices, breastfeeding schedule, and adequate nutrition intake. Conclusion: To support the implementation of breastfeeding at workplace, there are several things that need to be prepared, both from the mother, family, and work environment. The preparation include knowledge, attitude, psychological, devices for express and storage breastmilk, pumping schedule, good quality nutrition intake, and understanding lactation management. In addition, breastfeeding work environment also support the success of breastfeeding among working mothers.